The importance of regional centres in the management of adults with congenital heart disease in Switzerland: a retrospective, multicentric cohort study (Swiss Medical Weekly, 2025)
OBJECTIVE: We aimed to assess the extent of cardiac-related hospitalisations among adult congenital heart disease (ACHD) patients followed at Swiss regional ACHD centres.BACKGROUND: In Switzerland, adult congenital heart disease patients are followed at specialised ACHD centres. According to the Swiss recommendations for standards of adult congenital heart disease care,ACHD centres are categorised as regional and supraregional centres. In contrast to regional centres, supraregional centres require staffing for congenital cardiac surgery and complex congenital cardiac interventions.METHODS: Adult congenital heart disease patients enrolled in the SACHER registry and followed at one of three regional ACHD centres (University Hospital Basel, St Gallen Cantonal Hospital, Lucerne Cantonal Hospital) from May 2014 to March 2022 were included. Data were abstracted by chart review and included demographics, clinical and surgical history, follow-up duration and cardiac-related hospitalisations during follow-up.RESULTS: In total, 1031 patients (accounting for 22% of patients from the entire SACHER cohort) were included (570 at University Hospital Basel, 231 at St Gallen Cantonal Hospital, 230 at Lucerne Cantonal Hospital). During a median (IQR) follow-up of 3 (1–5) years, there were 237 hospitalisations (100 [42%] emergencies) among 136 (13%) patients. The majority of admissions (157, 66%), occurred at the regional centre. Arrhythmias (49 of 64 admissions, 77%) and heart failure hospitalisations (26 of 34, 76%) were mainly managed locally. The main reasons for referral to supraregional ACHD centres were heart surgery (32/56, 57%) and complex structural percutaneous interventions (pulmonary valve replacement [3/3, 100%] and balloon dilation of aortic coarctation [7/7, 100%]).CONCLUSION: In Switzerland, regional ACHD centres provide an important contribution to the management of the growing cohort of adult congenital heart disease patients. Most hospitalisations were managed locally. This was particularly true for emergencies, arrhythmia and heart failure hospitalisations. The main reasons for referral to supraregional ACHD centres were complex percutaneous interventions.